WEATHERING STAGE OF TILL AND GLACIAL HISTORY OF THE CENTRAL SØR RONDANE MOUNTAINS, EAST ANTARCTICA - モリワキ, キイチ; ヒラカワ, カズオミ; マツオカ, ノリカズ; MORIWAKI, Kiichi; HIRAKAWA, Kazuomi; MATSUOKA, Norikazu (National Institute of Polar Research, 1991)
P(論文) The Sør Rondane Mountains are in some places covered with tills which show various degrees of weathering. According to the degree of weathering, tills are classified into five exposure stages (relative ages), which are roughly correlated with absolute ages obtained by NISHIIZUMI et al. (Earth Planet. Sci. Lett., 104,440,1991). On the basis of height and age data of tills, the glacial history in the central Sør Rondane is constructed as follows : (1) A large part of the Mountains was once covered with an ice sheet (prior to 4 Ma); (2) The ice sheet retreated intermittently prior to 1 Ma; (3) In the first half of the last one million years, the ice sheet was stagnant or re-advanced, forming lateral moraines in some places. The ice sheet surface was up to about 100m higher than the present in that age; (4) Since then, the ice sheet retreated to the level somewhat higher than the present one until tens of thousands years ago. departmental bulletin paper